PADRÕES ESTRUTURAIS E FUNCIONAIS DAS PAISAGENS RIPÁRIAS DOS RIOS PITANGUI E JOTUBA NO PRIMEIRO PLANALTO PARANAENSE PONTA GROSSA 2012 - Pereira, Tiaro Katu (2012)
Landscape Ecology is the science that studies the relationship between structural patterns and processes acting in the landscape. It concerns nowadays about searching suitable parameters for ecological modeling in spatial distributions. This study analyzes the Pitangui and Jotuba riparian zones in the First Paraná Plateau, trying to settle a landscape model in forest/field riparian ecotones. The areas were delineated from 2001 orthophotos (1:10,000), including all native vegetation in flooding limits of the lotic channels. The landscape units (UP) were represented by the Alluvial Ombrophilous Mixed Forest metacommunity (FOMA) including as phytocoenosis both the riparian woody forest (FR) and hydrophilous vegetation (VH). Landscape metrics and statistical treatment were used to characterize landscapes and patches. To evaluate the FR patches we presumed a 30 m edge. Pitangui river (1,072 ha) has the double of the riparian area of Jotuba river (539 ha), although proportionally both were UPs equivalent (40% of FR and 60% of VH). Both rivers have a large number of small rounded patches and relatively few large areas that trend to more complex and irregular shapes with the area increases. Also smaller patches are more spatially heterogeneous than the greater ones, more aggregated along the river channel. 60% of FR area on both rivers are under edge effect. Pitangui has 91 core areas linked by 69 corridors and Jotuba River has 53 core areas with 47 corridors. In the riparian zones, VH areas occupy the flood plains showing higher variability in size and spatial distribution. This summarize the natural fragmentation remarks for the riparian vegetation of regional rivers at South Brazil.x